2022
DOI: 10.1017/aae.2022.26
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Subsidies on Persistent and Transient Technical Inefficiency: Evidence from Polish Dairy Farms

Abstract: We investigate the impact of five types of subsidies granted under the European Union Common Agricultural Policy on the persistent and transient inefficiency of Polish dairy farms. Our research shows that coupled and environmental subsidies reduce transient technical inefficiency, while the opposite is true for Less Favoured Areas (LFA) and other rural subsidies. Simultaneously, environmental, LFA, and other rural subsidies increase persistent technical inefficiency. These results imply that the impact of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Contrastingly, direct subsidies to the R&D of incumbent food manufacturers should be carefully reviewed because they encourage the survival and expansion of low‐productivity firms (Acemoglu et al, 2018). Moreover, Pisulewski and Marzec (2022) found that subsidies increase persistent technical inefficiency in the dairy sector.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Contrastingly, direct subsidies to the R&D of incumbent food manufacturers should be carefully reviewed because they encourage the survival and expansion of low‐productivity firms (Acemoglu et al, 2018). Moreover, Pisulewski and Marzec (2022) found that subsidies increase persistent technical inefficiency in the dairy sector.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Given this reality, the relevance of considering this aspect when devising a state financial support program for animal husbandry becomes particularly pronounced during times of war and post-war transition, given the heightened vulnerability of small enterprises in such crisis contexts. Moreover, research by Petrick & Götz (2019) underscores that state subsidies foster a higher growth rate in the cow population within small farms compared to agro-holdings.…”
Section: Ways To Improve the Current State Of The Dairy Industry Of U...mentioning
confidence: 99%
“…Polish dairy farms are rather small, and the impact of COVID-19 was rather small. Poland's accession to the EU in 2004 created good prospects for dairy farms (Pisiulewski and Marzec 2022). So, summing up, the COVID-19 pandemic had a tremendous impact on dairy supply chains because they are vulnerable to shock (Karwasra et al 2021).…”
mentioning
confidence: 99%